2017
DOI: 10.1111/ics.12425
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide diversity of scalp seborrhoea, as daily experienced by seven human ethnic groups

Abstract: The kinetics and slopes of the re-greasing process of the human scalp appear similar in all ethnic groups studied. However, striking quantitative differences are found between the seven ethnic groups, resulting from different sebaceous production levels and scalp hygiene routines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
2
7
0
2
Order By: Relevance
“…The average amount of sebum in the scalp of men is about 1.5 times higher than that of women. This sebum amount result is consistent with that from another study performed by L'Oreal [13]. There is less amount of ceramide present in the horny layer of men's scalp.…”
Section: Basic Features Of Scalp: Sex and Racessupporting
confidence: 91%
“…The average amount of sebum in the scalp of men is about 1.5 times higher than that of women. This sebum amount result is consistent with that from another study performed by L'Oreal [13]. There is less amount of ceramide present in the horny layer of men's scalp.…”
Section: Basic Features Of Scalp: Sex and Racessupporting
confidence: 91%
“…It seems that the balance interaction between host and commensal bacteria plays a significant role in dandruff pathogenesis. 10,11 Our study also showed that the sebum in our dandruff subjects hijab or non hijab still within normal level compared to the data of Thailand population (15 μg/cm 2 ), 12 while the TEWL from our study higher than normal level (13 g/m 2 /h). 13 These findings support that dandruff as a mild form of seborrhoic dermatitis is a manifestation of skin barrier disfunction, which showed increasing of TEWL.…”
Section: Acknowledgementssupporting
confidence: 70%
“…Previous studies have suggested a prominent role of host-associated physiological factors in the manifestation of dandruff (Xu et al, 2016 ; Pouradier et al, 2017 ). A systematic investigation of the host physiological parameters was carried out to study the association of host physiology with dandruff and with the scalp microbiome (Table S2 ).…”
Section: Resultsmentioning
confidence: 95%
“…Due to the inherent diversity in ethnicity, climatic conditions, diet, and other factors, a distinct microbial diversity was anticipated in the Indian population, which was evident from the high abundance of uncultured Malassezia sp. in the scalp microbiome (Pouradier et al, 2017 ). These observations necessitate the strain-level in vitro characterization of the unknown Malassezia species to identify population-specific biomarkers, and to understand their possible role in the etiology of dandruff in the various populations.…”
Section: Discussionmentioning
confidence: 99%